Cytotoxicity evaluation and apoptosis-inducing effects of furanone analogues in insect cell line SL2 - Yuanhang Ren (Taylor & Francis Group, 2018)
Insecticides containing furan ring have attracted more attention owing to their unique mechanism of action. 25 furanone analogues were used to conduct a preliminary screening on insect cell line SL2 and these compounds exhibited good cytoactivity. Particularly, compound 14 presented good inhibitory effect with an IC50 value of 28.14 μM. Subsequently, we investigated the selectivity against insect cells by testing the cytotoxicity of it on human cell line HEK293 and we noticed that compound 14 was less toxicity than the reference insect cells. Finally, we attempted to illustrate the act mechanism of compound 14 on SL2 cells at the cellular level and found it initiated apoptosis through a caspase-dependent mitochondrial pathway that down-regulated mitochondrial membrane potential level, increased the activity of caspase-3 and altered the cell cycle. The result showed that compound 14 could be considered as a new potent insecticide to be used for further optimization.